Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Eugene Armstrong, December 26, 1988 - Armstrong, Eugeneet al (1988)
Iowa Christmas bird counts of species found in Des Moines contributed by Eugene Armstrong, December 26, 1988. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1988-1989. Epson - sheet feed